Strategi Pemerintah Kota Banda Aceh dan Kota Surakarta dalam Mewujudkan Kota Ramah Disabilitas - Adi Suhendra (Research and Development Agency Ministry of Home Affairs, 2017)
This study is about disability-friendly cities (KRD). This research is motivated by the innovation of local government policy in realizing the city of disability friendly. The purpose of this research is to describe various efforts made by local government of Banda Aceh City and Surakarta City in realizing KRD. This research uses qualitative approach. The data collection technique is done by interviewing informants and collecting secondary data. While data processing is done by data reduction is open coding, axial coding and selective coding. The findings of the strategy in the city of Surakarta is to support the budget for the disabled. In addition, the local government of Surakarta also issued social assistance given to persons with disabilities who enter the criteria of poor families. While Banda Aceh, local government do dukunyan in the field of education that is by establishing schools in Kota For kindergarten level there are six units, 20 units of elementary school, nine units of junior high school, seven units of SMA, and 15 SLB with the number of supporters of 120 teachers. In the housing sector, Pemko Banda Aceh also issued a policy to enable disabled people to access affordable housing facilities and the assistance of Al-Quran Braile Digital to the blind. The result of this research is surakarta city make KRD by giving social support. While Banda Aceh is more on creating an inclusive city that unites people with disabilities to merge in people’s lives.